2003
DOI: 10.1007/bf03018367
|View full text |Cite
|
Sign up to set email alerts
|

Mini-dose (0.05 mg) intrathecal morphine provides effective analgesia after transurethral resection of the prostate

Abstract: P Pu ur rp po os se e: : To determine the optimal dose of intrathecal morphine that produces satisfactory analgesia with minimum side effects in elderly patients undergoing transurethral resection of the prostate (TURP). M Me et th ho od ds s: :In this double-blind prospective study, 42 patients undergoing TURP with spinal anesthesia were allocated to one of three groups. Group A (n = 14) received tetracaine, 10 mg, alone. Group B (n = 13) and Group C (n = 15) received morphine 0.05 mg and 0.10 mg, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…It is not known whether 0.05 mg of intrathecal morphine is the optimal dose for seniors undergoing bipolar hip prosthesis, but the dose-dependent effect would not need to be evaluated because it has been reported that 0.1 mg of intrathecal morphine showed good analgesic results after THA [3]. Although we found no disadvantageous effects, further study is needed to clarify the safety of intrathecal morphine for seniors.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is not known whether 0.05 mg of intrathecal morphine is the optimal dose for seniors undergoing bipolar hip prosthesis, but the dose-dependent effect would not need to be evaluated because it has been reported that 0.1 mg of intrathecal morphine showed good analgesic results after THA [3]. Although we found no disadvantageous effects, further study is needed to clarify the safety of intrathecal morphine for seniors.…”
Section: Discussionmentioning
confidence: 69%
“…Intrathecal morphine is associated with adverse effects, including respiratory depression, pruritus, and nausea [1][2][3][4][12][13][14]. Palmer et al [15] reported the disadvantageous effects of an increased dose of intrathecal morphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zahlreichen Studien, die intrathe kale Morphingaben mit ≤0,25 mg unter suchten, wurde keine Atemdepression be obachtet [1,2,5,7,14,17,28,33]. Vereinzelt werden aber auch Atemdepressionen be schrieben, sodass das diesbezügliche Ri siko auch bei geringen Dosierungen von intrathekal verabreichtem Morphin nicht ausgeschlossen werden kann [21,24] In einer früheren Untersuchung führ te die Kombination von 100 mg Indome thacin zu einer Spinalanästhesie mit Zu satz von Morphin und Fentanyl zu einer Verzögerung der ersten Analgetikaanfor derung von 9 auf 39 h [26].…”
Section: Atemdepressionunclassified
“…The addition of morphine to spinal anesthesia has been used effectively for postoperative analgesia after TURP [2][3][4]. Cunningham et al showed that one mg of spinal morphine produces excellent postoperative analgesia with considerable frequency of nausea or vomiting, pruritus, and danger of delayed respiratory depression [2].…”
Section: Introductionmentioning
confidence: 99%